Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Literasi Matematika Berdasarkan Prosedur Newman - Umar, Ali; Sartika, Lenis Ayu (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2023)
This research aimed to analyze students' mathematical literacy using the Newman's procedure. The research method employed qualitative descriptive. The research subjects were three students with high, medium, and low abilities in a Junior Hight School in Aceh Tengah Regency. The research findings indicated that, by using Newman's procedure, students with high, medium, and low abilities demonstrated similar skills in the aspects of reading and understanding problems. However, in the aspects of transformation, process skills, and writing final answers, differences in abilities were observed among students with high, medium, and low abilities.